Family Socioeconomic Status and Adolescent Depressive Symptoms in a Chinese Low– and Middle– Income Sample: The Indirect Effects of Maternal Care and Adolescent Sense of Coherence - Xu, Fuzhen; Cui, Wei; Xing, Tingting; Parkinson, Monika (Frontiers in Psychology, 2019)
The current study investigated whether socioeconomic status (SES) was associated with adolescent depressive symptoms through maternal parenting and adolescent sense of coherence (SOC). Using a sample of 1220 Chinese adolescents, it was found that socioeconomic status (SES), maternal care, and adolescent SOC were positively related to each other and negatively related to adolescent depressive symptoms respectively. Maternal control was positively related to adolescent depressive symptoms and negatively related to their SOC, but not significantly to SES. By analysis of structural equation modeling, we found that SES was associated with adolescent depressive symptoms indirectly through maternal care separately, as well as through maternal care and adolescent SOC sequentially. This study extended our understanding by showing possible indirect pathways by which family contextual factors and individual internal resource for adolescent depressive symptoms may operate separately and sequentially. The overall results highlighted the need to study adolescent depressive symptoms to find external and internal positive factors for maintaining adolescent emotional health, especially in families with relatively lower income.